Implikasi Pandemi Covid-19 Terhadap Meningkatnya Angka Perceraian: Studi Kasus Di Kota Gorontalo (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to conduct a study on the causes of marital breakdown and the impact of the COVID-19 pandemic on divorces in Gorontalo City. The author utilized an empirical juridical research method with a qualitative approach and employed descriptive methods. The research findings indicate that the main factors leading to divorces in Gorontalo City in recent months are as follows: physical and psychological violence, infidelity, lack of husband's responsibility in providing for the wife and children, and extremely poor communication. Additionally, data from various divorce cases in different regions, along with information from the Gorontalo Family Court, demonstrate that the COVID-19 pandemic has implications for divorce rates, including in Gorontalo City. One of the reasons for the increased divorce rates is partner violence due to stress and decreased financial income resulting from the pandemic situation.